Profile of vitiligo patients and distribution of narrowband-UVB therapy at dr. Cipto Mangunkusumo General Hospital - Suseno, Lis Surachmiati; Sukma, Putu Martha Gerynda; Rihatmadja, Rahadi; Agustin, Triana; Rahmayunita, Githa; Novianto, Endi (UI Scholars Hub, 2018)
Background: Vitiligo is a disease marked by depigmented macules. Prevalence of vitiligo varies between 0.1- 2.3% worldwide. The objectives of this study are to identify the socio-demographic profile of vitiligo patients and distribution of narrowband-UVB given as a treatment modality. However, in Indonesia, including at dr. Cipto Mangunkusumo General Hospital, there has not been any study on the profile of vitiligo patients. Therefore, a preliminary study on the patients’ profile would be very useful for healthcare providers in calculating the need for narrowband-UVB equipment and evaluation of its current use. Methods: A retrospective descriptive study, using secondary data obtained from dr. Cipto Mangunkusumo General Hospital medical records during the period of 2015-2017. Results: There were 255 vitiligo patients enrolled. Females were greater in number (55.3%). Most patients were distributed evenly in all age groups, highest number of patients were the 21-30 years age group (18.8%). Most patients received elementary school–high school education (56.9%), worked as private employees (36.9%), resided in Jakarta (47.8%). The common diagnosis were unspecified vitiligo (53.3%). Onset of symptoms were mostly around 2 months prior to diagnosis (38.8%) and most of the patients received other treatments other than narrowband-UVB (N=180, 70.6%). Conclusion: The number of vitiligo cases decreased each year with the average vitiligo cases of 85 cases per year and mostly women whereas the number of unspecified vitiligo were quite high. Therefore, more attention is needed from the physicians to treat the patient starting from the establishment of vitiligo to the decision treating with narrowband-UVB.